Utilizing Women In The Buddha In The Attic (2011) by Julie Otsuka - Ulfa Rimadini; An Fauzia Rozani Syafe'i (English Language and Literature, 2020)
This thesis is the analysis of a novel which written by Julie Otsuka entitled The Buddha In The Attic (2011). It explores the issue about utilizing women. It is also intended to find out the contribution of fictional devices such as character, plot, and setting in revealing the issue of utilizing women. This analysis is related to the concept of  exploitation and subordination from Kamla Bhasin that is supported by the text-based and context-based interpretation. The result of this analysis shows women are subordinated and exploited by men.